2022
DOI: 10.3389/fmars.2022.800423
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Foureye Butterflyfish (Chaetodon capistratus) and Symbiodiniaceae on the Transmission of Stony Coral Tissue Loss Disease

Abstract: Marine diseases have caused large scale decreases in coral cover across the Caribbean and are unfortunately projected to increase as sea surface temperatures rise. Identifying the main drivers of disease transmission is essential for our understanding and response to diseases in the future. This study investigates the effects of direct-contact, waterborne, Symbiodiniaceae composition, and butterflyfish foraging on the transmission rates of stony coral tissue loss disease (SCTLD) across Montastraea cavernosa (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…Although the etiological agent(s) responsible for SCTLD is (are) still unknown, various studies have suggested multiple vectors of transmission. Laboratory studies have demonstrated rapid and successful transmission via direct contact with a diseased colony (Aeby et al, 2019;Eaton et al, 2021;Titus et al, 2022), tank water shared with a diseased colony (Aeby et al, 2019;Aeby et al, 2021;Meiling et al, 2021), and indirect exposure to sediment that has contacted a diseased colony (Studivan et al, 2022b). All three modes (direct contact, waterborne, and sediment) are successful in intraand inter-species SCTLD transmission experiments, though varying levels of susceptibility are reported as discussed above (Aeby et al, 2019;Eaton et al, 2021;Meiling et al, 2021;Studivan et al, 2022b).…”
Section: Sctld Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the etiological agent(s) responsible for SCTLD is (are) still unknown, various studies have suggested multiple vectors of transmission. Laboratory studies have demonstrated rapid and successful transmission via direct contact with a diseased colony (Aeby et al, 2019;Eaton et al, 2021;Titus et al, 2022), tank water shared with a diseased colony (Aeby et al, 2019;Aeby et al, 2021;Meiling et al, 2021), and indirect exposure to sediment that has contacted a diseased colony (Studivan et al, 2022b). All three modes (direct contact, waterborne, and sediment) are successful in intraand inter-species SCTLD transmission experiments, though varying levels of susceptibility are reported as discussed above (Aeby et al, 2019;Eaton et al, 2021;Meiling et al, 2021;Studivan et al, 2022b).…”
Section: Sctld Transmissionmentioning
confidence: 99%
“…Finally, various lab-based SCTLD assays and molecular-based studies show significant involvement of the Symbiodiniaceae (Deutsch et al, 2021;Meiling et al, 2021;Titus et al, 2022;Williamson et al, 2022;Beavers et al, 2023). Notably, Beavers et al (2023) found increased expression of rab7, a known marker of Symbiodiniaceae degradation.…”
Section: Sctld Causes Symbiodiniaceaehost Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, M. capitata colonies dominated by Durusdinium had higher resistance to bleaching, but increased disease susceptibility. In a transmission experiment, M. cavernosa colonies that harbored higher abundances of Durusdinium were more susceptible to SCTLD than M. cavernosa colonies harboring Cladocopium, further suggesting that symbiont communities can play a significant role in a coral's susceptibility and resistance to SCTLD (Titus et al, 2022) Conversely, ex situ research on manipulated colonies found that corals associating predominantly with Cladocopium and Durusdinium were significantly less likely to contract SCTLD and form lesions than colonies associating predominantly with Breviolum (Dennison et al, 2021). Orbicella faveolata colonies sampled in Florida in 2015 were mostly Durusdinium dominated.…”
Section: A B Figurementioning
confidence: 96%
“…Other research pointed to ballast water as a likely spreader, in which release of ballast water too close to a reef could release the contagion into the seawater of an uninfected area (Rosenau et al, 2021;Studivan et al, 2022). Even within a reef, corallivorous fish seem to preferentially feed on diseased tissue and may aid in either transmission or recovery of the disease (Noonan and Childress, 2020;Titus et al, 2022). Regardless, multiple tank-based experiments show that within weeks of residing in proximity to a diseased colony, susceptible coral species will succumb to the disease (Aeby et al, 2019;Meiling et al, 2021;Huntley et al, 2022).…”
Section: Stony Coral Tissue Loss Diseasementioning
confidence: 99%